Eight new species of Cycloneuroterus Melika & Tang gallwasps from Taiwan and mainland China (Hymenoptera: Cynipidae: Cynipini) - Tang, Chang-Ti; Sinclair, Frazer; Hearn, Jack; Yang, Man-Miao; Stone, Graham N.; Nicholls, James A.; Schwéger, Szabina; Melika, George (Zootaxa, 2016)
Eight new species of cynipid gallwasps, Cycloneuroterus abei Melika & Tang, C. ergei Tang & Melika, C. gilvus Melika & Tang, C. globosus Melika & Tang, C. jianwui Tang & Melika, C. lohsei Melika & Tang, C. tumiclavus Tang & Melika, C. uraianus Tang & Melika, from Taiwan and mainland China are described. Descriptions, diagnoses, biology, and host associations for the new species and a key to all Cycloneuroterus species are given. All taxa are supported by morphological and molecular data. Seven newly described species induce galls on Quercus subgenus Cyclobalanopsis, while one, C. uraianus, induces galls on Castanopsis. This is the first Cycloneuroterus species known to associate with Castanopsis.